Educational scholarship and Ph.D. curriculum of medical education in Iran: A serious critique and a proposal - Eshagh Moradi (Zanjan University of Medical Sciences and Health Services, 2023)
Medical education as a discipline currently accepts students with two M.Sc. and Ph.D. degrees in Iran. This Ph.D. course was approved by the Curriculum Council Committee in Medical Sciences in 1386 AH (2016 AD). The curriculum of medical education has a total of 50 credits (including core: 20, non-core: 8, and dissertation: 22), which subsume various courses and topics such as student assessment, curriculum planning, educational leadership, program and teacher evaluation, qualitative research, educational research, clinical teaching, and so on (1). One of the necessary competencies expected from graduates of Ph.D. in medical education in Iran is to be able to have activity and innovation in various units of the Education Development Center (EDC), and it is necessary to acquire knowledge and skills about these units. One of these units is the "educational scholarship" unit, which performs various activities such as consulting, writing, and activities in the field of innovative and educational projects. The serious critique of the curriculum is that no course credit related to educational scholarship has been considered in the Ph.D. curriculum of medical education, so there is no time and program to teach this important topic to Ph.D. students of medical education, while it is one of their necessary and expected competencies. The absence of an educational program will lead to a lack of learning, and as a result, the student will not be empowered in this field. The proposal that is presented is that a 2-credit course (1 theoretical and 1 practical credit) with the title "Educational Scholarship" be placed in the curriculum of Ph.D. medical education (as a core course).